Cracking the Crimson Conundrum: a Case Report on Granulomatous Rosacea - Akshay Jain Salecha; Kode Sridevi; Akhila Merin John; Lakamsani Nagapadma; Damaraju Venkata Satya Ramamurthy (Berkala Ilmu Kesehatan Kulit dan Kelamin (Periodical of Dermatology and Venerology))
Background: Rosacea, a prevalent inflammatory skin condition, commonly affects the central facial area. Granulomatous rosacea, a rare variant of rosacea, presents diagnostic intricacies due to its clinical and histopathological resemblance to other granulomatous dermatoses. Purpose: We are presenting this case due to the scarcity of granulomatous rosacea cases, often misdiagnosed, leading to unwarranted treatment options. We describe a case of granulomatous rosacea in a 24-year-old female, elucidating clinical features and diagnostic challenges the patient presented with red, elevated lesions over the central facial region for three months. Clinical examination revealed well-defined erythematous papules. Dermoscopy and histopathological examination confirmed the diagnosis. Discussion: Granulomatous rosacea poses a diagnostic problem, necessitating early recognition and tailored management to prevent facial disfigurement and psychological distress. Differential diagnoses often require careful consideration and may involve a combination of clinical, dermoscopic, and histopathological assessments. Conclusion: This case underscores the importance of considering granulomatous rosacea in the differential diagnosis of other facial dermatoses.